Utility of platelet indices in diagnosing the underlying cause of thrombocytopenia due to accelerated platelet destruction - Yalavarthi, Sushma; Halder, Nirvana Rasaily; Pagidikalava, Aparna (Annals of Pathology and Laboratory Medicine, 2018)
Background: Thrombocytopenia is a common clinical manifestation of many diseases and has numerous causes, including decreased bone marrow production, increased spleen sequestration, and accelerated destruction of platelets. Among the various aetiologies, Accelerated platelet destruction is the most common cause. Distinction between the various aetiological categories of thrombocytopenia is usually made by invasive bone marrow examination. Some studies stated that Platelet indices were altered in various causes of thrombocytopenia and helpful in discriminating the causes. we aim, to know the role of platelet indices in determining the underlying cause of thrombocytopenia due to platelet destruction. Methods: Â 30 Healthy controls and 145 patients (study group) with thrombocytopenia (platelet count <150x109) were included in the study. Thrombocytopenia due to decreased bonemarrow production and artefactual thrombocytopenia were excluded. The study group was divided into 3groups. Group 1 includes immune thrombocytopenia, Group 2 having thrombocytopenia of non immunological causes and Group 3 includes miscellaneous causes. Clinical features, Platelet counts and platelet indices were studied and statistical analysis was performed.Â Result: In all the groups of thrombocytopenia due to accelerated platelet destruction, MPV and P-LCR were significantly higher; P-LCC was significantly lower than healthy controls. There was no significant variation of PDW in NonImmune thrombocytopenia and miscellaneous groups, but PDW was significantly lower in immune thrombocytopenia than healthy controls. Conclusion: Platelet indices should be considered in the diagnosis of thrombocytopenia due to accelerated destruction of any cause.Â Among the platelet indices, PDW can be useful for a positive diagnosis of immunological thrombocytopenia. DOI:10.21276/APALM.1717